EXPERIENTIAL PEDAGOGY FOR DEVELOPING EMPATHY IN FUTURE TEACHERS - Elena Ivanova Nedeva (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This article presents an innovative experiential learning model developed for prospective teachers within a university course on supporting children with chronic illnesses and their families. The model incorporates rhythmic group synchronisation exercises, emotionally resonant storytelling, real-life video testimonies, student-created theatrical performances, and a guided closed-eye visualisation—one of the most impactful elements. These practices are designed to foster empathy, emotional literacy, and inclusive pedagogical competence. During the course, students metaphorically represent illness through original stories, deliberately avoiding diagnostic labels to reduce stigma. These narratives are subsequently transformed into short theatrical performances, enabling participants to embody both physically and emotionally the lived experiences of children with chronic conditions. A mixed-methods evaluation was conducted, incorporating a structured classroom observation tool to assess students’ engagement, emotional responses, initiative, and collaboration. A post-course Likert-scale questionnaire measured students’ self-assessed development of empathy and their readiness for inclusive pedagogical practice. The results indicated strong alignment between observed behaviours and participants’ self-assessments. Grounded in the theories of experiential learning (Dewey, Kolb), social constructivism (Vygotsky), narrative pedagogy (Freire), multiple intelligences (Gardner), and socio-emotional learning (CASEL), the model provides a replicable and emotionally engaging approach to preparing future teachers for work in inclusive educational contexts.